Aluminum adsorption and antimonite oxidation dominantly regulate antimony solubility in soils. (December 2022) - Liu, Yan-Qing; Wen-Xin Lv,; Zhong-Qiu Zhao,; Yang, Yu-Ping; Zhang, Li-Xin; Wang, Li-Ying; Jing, Chuan-Yong; Duan, Gui-Lan; Zhu, Yong-Guan
Abstract: Soil antimony (Sb) contamination occurs globally due to natural processes and human activities. Total Sb concentration in soils fails to assess its ecological risk, while determined by the concentration of available Sb, which is readily for biological uptake. Available Sb in different soils varied significantly according to soil properties. However, so far it is unknown how soil properties regulate Sb availability, and no model has been established to predict it through soil properties. In this study, 19 soils spiked with antimonite [Sb(III)] were used to identify the major factors controlling Sb availability and establish its predicting models. The results showed that available Sb in different soils varied largely depending on the contents of free aluminum (fAl), free iron (fFe) and electric conductivity (EC), which explained 33%, 27% and 24.9% of the total variation, respectively. During the first 42 days of soil aging, fAl and EC effectively predicted the concentrations of available Sb with R 2 = 0.64, while during the later stages (70–150 d) of soil aging, fAl content was the unique parameter employed into the predicting model (R 2 = 0.53). These results firstly demonstrate that the content of free aluminum (fAl) is the most important factor regulating Sb availability in soils, although the content of fAl is much lower than that of fFe. This finding can help to develop new remediation materials for Sb-contaminated soils. The prediction models can provide promising tools of assessing the ecological risk. In addition, Sb availability was also affected by the oxidation of Sb(III). After 150 days aging, 1–61% of Sb(III) was oxidized to pentavalent Sb [Sb(V)], which was significantly positively correlated with available Sb, suggesting that Sb(III) oxidization mobilizes Sb in soils. All these findings would help to understand Sb migration and transformation in soils, and to develop new strategies for remediating Sb-contaminated soils. Graphical abstract: Image 1 Highlights: Free Al content is the most important factor regulating Sb solubility in soils. Soil Sb availability can be reliably predicted based on Al content and EC. Soil Al/Fe-oxides are negatively correlated with Sb availability. Soil EC and pH are positively correlated with Sb availability. The oxidation of Sb(Ⅲ) to Sb(V) increases Sb availability.